La alimentación: un estudio histórico cultural (Estudios de Historia de España, 2017)
Specially for the man, the act of feeding includes a complex set of meanings: feeding, together with dressing and house, is one of his more urgent necessities,that every time imposes him its own cultural norms and challenges of subsistence.Our intention is to propose a theoretical nourishing system, to analyze and to integrate the concepts that define it and to offer a demonstrative and illustrative historical frame.In this system the representative elements are: the models of alimentation and the circuit:Production/Supplying/Consumption; where as the time proposal is the Latter Middle Age, specially hispanic.
Keywords: Food; Later Middle Ages; Spain